The function of self-deception in conformists - Hrgović, Josip; Hromatko, Ivana (2005)
Self-deception is one of the most complex cognitive-behavioral mechanisms resulting from an interaction of individuals within a group. Previous studies of self-deception as an adaptive phenomenon (whether conducted from ultimate, evolutionary perspective or distal and proximate, psychological/psychiatric/social perspectives) gave inconsistent results. According to a social-brain hypothesis, the growth of social complexity influenced the evolution of more and more complex cognitive-behavioral patterns in social animals. Accordingly, anxiety, depression and self-deception should be a consequence of individuals' status within a group. The aim of this experiment was to test whether persons with discrepancy in their publicly vs. privately stated opinions differ from the rest of the population in levels of self-deception, anxiety and depression. The results show that a change in opinion which occurs after the group pressure has ceased is related to greater levels of self-deception as well as depression. Theoretical implications of results are discussed in terms of evolutionary adaptiveness of self-deception.
Projekt MZOS
Projekt MZOS
ENG